Effect of Taurine Supplementation on Growth Response and Body Composition of Largemouth Bass. (2nd April 2016) - Frederick, Catherine A.; Coyle, Shawn D.; Durborow, Robert M.; Bright, Leigh Anne; Tidwell, James H.
Abstract: Taurine is "conditionally essential" for some fish species, particularly when fish meal levels in their diets are reduced. Taurine supplementation has not yet been evaluated in the Largemouth Bass Micropterus salmoides . A 12-week feeding trial was conducted using a 2 × 2 factorial design with the main effects being fish meal inclusion (0% or 30%) or taurine supplementation (0% or 2%). The fish meal diets contained sardine fish meal while the nonfish meal diets used pork meal, which has a very low taurine content, as the animal source protein. The four experimental diets were formulated to contain 40% crude protein and 12% lipid. The feeding trial was conducted using juvenile Largemouth Bass (19.3 ± 3.9 g; mean ± SD) stocked at 25 fish/tank into twelve 230-L aquaria within a recirculating system. Fish were fed to apparent satiation twice daily. Dissolved oxygen, pH, and temperature were monitored daily, while alkalinity, total ammonia nitrogen, and nitrite-nitrogen were monitored three times weekly. Analysis of harvest data indicated a significant statistical interaction between fish meal inclusion and taurine supplementation only for feed conversion ratio (FCR). In diets containing no fish meal, the addition of taurine significantly increased the FCR (from 2.2 to 2.6). However, in fish fed diets containing fish meal, supplemental taurine significantly decreased the FCR (from 2.2 to 1.9). In terms of main effects, taurine supplementation did not significantly affect any of the measured growth or survival variables. Survival and growth in Largemouth Bass fed 0% fish meal were not significantly different from survival and growth in those fed 30% fish meal. Body composition variables were not significantly affected by either fish meal inclusion or taurine supplementation. These data support previous studies that found that by-products from terrestrial animal sources can successfully replace fish meal in diets for Largemouth Bass. These data also indicate that Largemouth Bass do not have a significant dietary requirement for taurine. Received March 27, 2015; accepted July 31, 2015